Consensus document on the management of febrile neutropenia in paediatric haematology and oncology patients of the Spanish Society of Pediatric Infectious Diseases (SEIP) and the Spanish Society of Pediatric Hematology and Oncology (SEHOP) - Leticia Martínez Campos; Paula Pérez-Albert; Laia Ferres Ramis; Elena María Rincón-López; Natalia Mendoza-Palomar; Pere Soler-Palacin; David Aguilera-Alonso (Elsevier, 2023)
Febrile neutropenia is one of the main infectious complications experienced by paediatric patients with blood or solid tumours, which, despite the advances in diagnosis and treatment, are still associated with a significant morbidity and mortality. These patients have several risk factors for infection, chief of which are chemotherapy-induced neutropenia, the disruption of cutaneous and mucosal barriers and the use of intravascular devices. Early diagnosis and treatment of febrile neutropenia episodes based on the patient's characteristics is essential in patients with blood and solid tumours to improve their outcomes. Therefore, it is important to develop protocols in order to optimise and standardise its management. In addition, the rational use of antibiotics, with careful adjustment of the duration of treatment and antimicrobial spectrum, is crucial to address the increase in antimicrobial drug resistance.The aim of this document, developed jointly by the Spanish Society of Pediatric Infectious Diseases and the Spanish Society of Pediatric Hematology and Oncology, is to provide consensus recommendations for the management of febrile neutropenia in paediatric oncology and haematology patients, including the initial evaluation, the stepwise approach to its treatment, supportive care and invasive fungal infection, which each facility then needs to adapt to the characteristics of its patients and local epidemiological trends. Resumen: La neutropenia febril es una de las principales complicaciones infecciosas que sufren los pacientes pediátricos oncohematológicos, y a pesar los avances en diagnóstico y tratamiento, siguen condicionando una mortalidad y morbilidad significativa. Estos pacientes agrupan una serie de factores de riesgo de infección, donde destaca la neutropenia asociada a quimioterapia, la disrupción de barreras cutáneo-mucosas y el uso de dispositivos intravasculares. El abordaje diagnóstico y terapéutico precoz de los episodios de neutropenia febril en los pacientes oncohematológicos, ajustado a las características individuales de cada paciente, es fundamental para mejorar su pronóstico. Por ello, diseñar protocolos de abordaje, que sistematicen su atención, permite optimizar y homogeneizar su abordaje. Además, racionalizar el uso de los antimicrobianos, ajustando la duración y el espectro de los mismos, es crucial para hacer frente al incremento de resistencias a antimicrobianos.El objetivo de este documento, elaborado entre la Sociedad Española de Infectología Pediátrica y la Sociedad Española de Hematología y Oncología Pediátrica, es dar recomendaciones de consenso sobre el manejo de la neutropenia febril en el paciente oncohematológico, respecto al abordaje inicial, terapia secuencial y de soporte e infección fúngica invasiva, que cada centro debe adaptar a las características de sus pacientes y epidemiología local.